KONSTRUKSI UJI KESESUAIAN MODEL GEOGRAPHICALLY WEIGHTED POLYNOMIAL REGRESSION - Nur Chamidah (Department of Mathematics, Hasanuddin University, 2019)
AbstractGeographically Weighted Polynomial Regression (GWPolR) is a generalization of Geographically Weighted Regression (GWR) model. By using the generalization, GWPolR has parameters much more than GWR model. In general, excess of the number of parameter will have a higher appropriate value. However, the model which has less parameter will have the excess for easing in application and its interpretation. Nevertheless, when the model has more the parameters, then the model will be better significantly to be used. Therefore, the aim of this paper is to construct the conformity between hypothesis test with respect to the GWPolR model. Keywords: Geographically weighted polynomial regression, Geographically Weighted Regression, uji kesesuaian model AbstrakGeographically Weighted Polynomial Regression (GWPolR) merupakan perumuman dari model Geographically Weighted Regression (GWR). Dengan perumuman tersebut, model GWPolR memiliki jumlah parameter yang lebih banyak daripada model GWR. Umumnya, kelebihan model dengan jumlah parameter lebih banyak adalah memiliki nilai kesesuaian lebih tinggi. Sebaliknya, model dengan jumlah parameter yang sedikit memiliki kelebihan berupa kemudahan dalam aplikasi dan interpretasinya. Namun demikian, jika model dengan jumlah parameter yang lebih banyak ternyata secara signifikan lebih baik maka sudah seharusnya model tersebut dipilih untuk digunakan. Oleh karena itu, tujuan paper ini adalah mengkonstruksi uji hipotesis kesesuaian model GWPolR. Kata Kunci: Geographically weighted polynomial regression, Geographically Weighted Regression, uji kesesuaian model